Occupational health and safety management: The use of personal protective equipment (PPEs) in Indonesian mechanical workshop - Nurul Aziza; Febria Listina; Regina Putri Mariantari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: A work accident occurs when an incident occurs during an industrial or related work process and results in the loss of time, property, or life. A work accident is an undesirable and often unpredictable event. Every year there are almost a thousand times more non-fatal work accidents than fatal work accidents. Purpose: To examine how the implementation of the use of Personal Protective Equipment (PPE) by workshop mechanics. Method: This type of research is descriptive qualitative. Data were collected through in-depth interviews with five informants: one key informant, one source informant, and three supporting informants. Each interview was conducted in one day, with a duration of no more than 30 minutes per respondent, using data analysis triangulation. Results: PT X has not implemented the use of PPE optimally, as it has not issued warnings or sanctions to its mechanics. The mechanics are also not yet aware of the importance of using complete PPE in carrying out their work. PT X has not conducted monitoring and evaluation of PPE. Conclusion: The ineffectiveness of the implementation of the use of PPE at PT X is due to the absence of strict regulations and sanctions given to mechanics, the lack of availability of PPE in various sizes for mechanics so that mechanics are less comfortable wearing all-size PPE. It is hoped that PT can enforce strict rules regarding PPE in the company, provide complete PPE and conduct monitoring and evaluation of the implementation of PPE.